1975
DOI: 10.1002/path.1711170404
|View full text |Cite
|
Sign up to set email alerts
|

Nature of muscular change in osteomalacia: Light‐ and electron‐microscope observations

Abstract: Thirteen muscle biopsy specimens (mainly the gluteus maximus) from 12 patients with laboratory confirmation of osteomalacia and proximal muscle weakness in 10 were examined by light and electron microscopy. Light microscopy revealed mild diffuse non-specific atrophy of the muscle fibres in 10 cases, severe generalised atrophy in one and patchy group atrophy in one. There was no myopathic change in specimens from cases with either a nutritional aetiology, or a mixed aetiology. The former, mostly women gave a hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
13
1
2

Year Published

1976
1976
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 20 publications
2
13
1
2
Order By: Relevance
“…Disuse from pain contributes very little to the symptomatology and is, moreover, common to all osteomalacias. We strongly feel that, even though some of the clinical material used by Dastur et al (1975) and here is the same, the nature of muscular change in osteomalacia of nutritional aetiology is no different from that due to other causes. Osteomalacia regardless of its aetiology is in fact a true reversible myopathy, as noted by others earlier.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Disuse from pain contributes very little to the symptomatology and is, moreover, common to all osteomalacias. We strongly feel that, even though some of the clinical material used by Dastur et al (1975) and here is the same, the nature of muscular change in osteomalacia of nutritional aetiology is no different from that due to other causes. Osteomalacia regardless of its aetiology is in fact a true reversible myopathy, as noted by others earlier.…”
Section: Discussionmentioning
confidence: 77%
“…To date light microscopy and occasional reports of electronmicroscopy (Smith and Stern, 1969;Stern ct al., 1973) have shown no signifi- Dastur et al (1975) maintain that on electronmicroscopy they found 'evidence of non-specific muscular atrophy in the nutritional group and degenerative changes which constitute a form of myopathy similar to those seen in muscular dystrophies in the group with a major added metabolic or endocrinal factor'. They contend that in nutritional osteomalacia no myopathy exists and the proximal muscle weakness is in the nature of an atrophy, a reflection of a combination of disuse and malnutrition of the musculature.…”
Section: Discussionmentioning
confidence: 97%
“…Probable mechanisms may be: upregulation of pro-inflammatory and down-regulation of anti-inflammatory cytokines [7,8,18,19], overstimulation of the renin-angiotensin system [5,6], proliferation of smooth muscle cells, and atrophy, degeneration, and or proliferation of cardiomyocytes [11,20,21], defects in heart cell calcium metabolism through regulation of calcium channel activity mediated by the cAMP pathway [22], remodeling of heart extracellular matrix metabolism mediated by matrix metalloproteinases [23], secondary hyperparathyroidism with its cardiac consequences [9,10], and many other less well-appreciated ones. In our study, there was no direct correlation between serum 25(OH)D 3 and its deficiency with LVEF and NYHA functional class.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D deficiency, in association with the patient's history of low serum ferritin, suggests that the patient may have had a nutritional or absorption defect to account for her illness. Vitamin D deficiency causes myopathy, but on histopathology minimal changes such as atrophy are the only features to be seen 4. Alternatively, parathyroid hormone is known to regulate body levels of a number of ions including magnesium, sodium, potassium, and bicarbonate 12.…”
Section: Discussionmentioning
confidence: 99%